IMPLEMENTATION OF THE PULL OUT LEARNING MODEL IN INCLUSIVE EDUCATION PROGRAMS TO OPTIMIZE THE DEVELOPMENT OF CHILDREN WITH SPECIAL NEEDS AT PELANGI ANAK NEGERI YOGYAKARTA ISLAMIC KINDERGARTEN - Salpina, Salpina; Putri, Dwi Adhinda Junaidi (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
Inclusive education is a form of implementation of the law article 31 paragraph 1 concerning education, because the purpose of inclusive education is to give children with special needs the same educational rights as normal children. In the implementation of inclusive education, it certainly requires a learning model that can help optimize the development of children with special needs, bearing in mind that the learning process for children with special needs requires special assistance so that it requires different learning strategies and models. Therefore, this study describes the pull out learning model used in the learning process of inclusive education at the Pelangi Anak Negeri Yogyakarta Islamic Kindergarten. The purpose of this research is to find out: 1) The implementation of inclusive education, 2) The application of the pull out learning model, 3) The implementation of the pull out learning model in optimizing the abilities of children with special needs. Data collection techniques used are observation, interviews and documentation. The data analysis was carried out in 3 stages, namely data reduction, data presentation, and drawing conclusions. The results of this study state that the application of the pull out learning model can help optimize the ability of children with special needs to balance the abilities of normal children.